2021
DOI: 10.3390/ijerph18116126
|View full text |Cite
|
Sign up to set email alerts
|

Urban Environment and Health: A Cross-Sectional Study of the Influence of Environmental Quality and Physical Activity on Blood Pressure

Abstract: Few studies have examined the relation between urban built environment and the prevalence of hypertension. This cross-sectional study aimed at assessing the relationship between the environmental quality, physical activity, and stress on hypertension among citizens of Kaunas city, Lithuania. We conducted a survey of 1086 citizens residing in 11 districts to determine their perceptions of environmental quality, health behavior, and health indices. The independent variables included residential traffic flows, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
1
4
0
1
Order By: Relevance
“…Living in the capital Beirut (crowded urban area) compared to Mount-Lebanon (peri-urban area) was positively associated to CHD. Living in Beirut exposes participants to higher levels of stress, in part due to exposure to various environmental factors, traffic-related air pollutants, noise, higher levels of violence, and lower social support, consistent with previous national 8 , 9 and international 44 , 45 studies. Similarly, the lack of green spaces in an urban area can negatively affect a person’s well-being and PA. 46 Previous works revealed that women may be more vulnerable to urbanization in terms of CVRFs (hypertension, psychiatric disorders) than men.…”
Section: Discussionsupporting
confidence: 86%
“…Living in the capital Beirut (crowded urban area) compared to Mount-Lebanon (peri-urban area) was positively associated to CHD. Living in Beirut exposes participants to higher levels of stress, in part due to exposure to various environmental factors, traffic-related air pollutants, noise, higher levels of violence, and lower social support, consistent with previous national 8 , 9 and international 44 , 45 studies. Similarly, the lack of green spaces in an urban area can negatively affect a person’s well-being and PA. 46 Previous works revealed that women may be more vulnerable to urbanization in terms of CVRFs (hypertension, psychiatric disorders) than men.…”
Section: Discussionsupporting
confidence: 86%
“…In particular: n = 2 were excluded because they referred to undergraduate students in college dorms [ 49 ] and children in daycare centers [ 50 ]. Thus, they were not coherent with the residential settings; also, a study by Srinivasan and Ram [ 51 ] was excluded because it was preliminary research that still lacks any results ( n = 1); in addition, although it was related to the scope of the research, the study by Grazuleviciene et al [ 52 ] was highly focused on blood pressure ( n = 1); instead, Singh [ 53 ] did not consider any of the IEQ parameters nor any housing conditions ( n = 1); in conclusion, other studies [ 54 , 55 , 56 , 57 , 58 ] were excluded because the authors did not find the full texts ( n = 5). …”
Section: Methodsmentioning
confidence: 99%
“…in addition, although it was related to the scope of the research, the study by Grazuleviciene et al [ 52 ] was highly focused on blood pressure ( n = 1);…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the methods of the participants’ enrolment as well as the description of the collaborative study have been provided previously [ 53 , 54 ]. The study was conducted in accordance with the Declaration of Helsinki [ 55 ] and were approved by the Kaunas Regional Committee for Biomedical Research Ethics (BE-2-51.…”
Section: Methodsmentioning
confidence: 99%